THE EFFECT OF SYNTHESIS PROCESS PARAMETERS ON THE PHYSICO-CHEMICAL PROPERTIES AND PHOTOCATALYTIC ACTIVITY OF PRISTINE AND ZrO₂-DOPED TiO₂ CATALYSTS - VASİĆ JOVEV, Marija; LJUPKOVİĆ, Radomir; STEPİĆ, Katarina; RANĐELOVİĆ, Marjan; MARINKOVİĆ, Miloš; ZARUBİCA, Aleksandra (Studia Universitatis Babeș-Bolyai Chemia, 2025)
In this study, TiO2-based catalysts were synthesized using a modified sol-gel method. The catalysts were prepared at two different pH values (10 and 13) and were subsequently doped with zirconia to improve their photocatalytic performance. The physico-chemical properties of the catalysts, including structural, textural, morphological, and thermal properties, were studied using XRD, BET, SEM, and TG/DTA methods, respectively. The photocatalytic activity of the synthesized catalysts was tested in the degradation/decolorization reaction of methylene blue dye. The results indicated that the synthesis parameters and zirconia doping had a significant impact on the catalysts' physico-chemical characteristics and, therefore, their activity. It can be pointed out that catalysts with improved properties and enhanced photocatalytic activity can be obtained by carefully selecting and optimizing synthesis conditions, as well as by modifying or doping them with a suitable dopant.